2010
DOI: 10.1203/00006450-201011001-01248
|View full text |Cite
|
Sign up to set email alerts
|

1248 Procollagen Type Iii Propeptide Levels Among Preterm Infants in Neonatal Intensive Care Unit

Abstract: Objective: to assess whether Doppler velocimetry is predictive of neonatal outcome in bichorionic and monochorionic twin pregnancies complicated by intrauterine growth restriction.Methods: were collected retrospectively data of all twin pregnancies complicated by intrauterine growth restriction during the period between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Similar to our findings in septic patients, serum concentration was increased in severely injured non-survivors and in those who had developed MOF. This agrees with the results reported by Said et al [ 20 ] and Zakynthinos et al [ 15 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Similar to our findings in septic patients, serum concentration was increased in severely injured non-survivors and in those who had developed MOF. This agrees with the results reported by Said et al [ 20 ] and Zakynthinos et al [ 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our findings, Said et al [ 20 ] assessed levels of PIIINP among preterm neonates and found that serum PIIINP was significantly higher in septic cases than in the controls. The highest levels were in the ventilated group, followed by the septic and grower groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation